FAKTOR YANG MENINGKATKAN KEJADIAN POST-OPERATIVE NAUSEA AND VOMITING (PONV) PADA PASIEN LAPARATOMI - Nurleli Nurleli; Ainal Mardhiah; Nilawati Nilawati (Universitas Prima Indonesia, 2021)
Post-operative Nausea and Vomiting (PONV) delay the patient's recovery period, inhibit activity, and have an impact on increasing the cost of care. This study aims to determine the factors associated with the incidence of post-operative nausea and vomiting in post-laparotomy patients. The research design was a descriptive cross-sectional study. Data collection was conducted from 18 June to 18 July 2019 on 30 respondents was selected by purposive sampling at the Meuraxa Hospital Banda Aceh. Data were processed into univariate and bivariate analysis using the Chi-Square test. The results showed a relationship between patient factors, anesthesia factors, and surgical factors with the incidence of PONV in post-laparotomy patients (P-value <0.05). The expected that health care providers in providing perioperative nursing care must focus on the factors that influence to eliminate the possibility of PONV so that it can improve patient comfort and speed up the recovery period.